Isoquercitrin Delays Denervated Soleus Muscle Atrophy by Inhibiting Oxidative Stress and Inflammation - Shen, Yuntian; Zhang, Qiuyu; Huang, Ziwei; Zhu, Jianwei; Qiu, Jiayi; Ma, Wenjing; Yang, Xiaoming; Ding, Fei; Sun, Hualin (Frontiers in Physiology, 2020)
Although denervated muscle atrophy is common, the underlying molecular mechanism remains unelucidated. We have previously found that oxidative stress and inflammatory response may be early events that trigger denervated muscle atrophy. Isoquercitrin is a biologically active flavonoid with antioxidative and anti-inflammatory properties. The present study investigated the effect of isoquercitrin on denervated muscle atrophy and its possible molecular mechanisms. We found that isoquercitrin was effective in alleviating muscle mass loss following denervation in a dose-dependent manner. Isoquercitrin demonstrated the optimal protective effect at 20 mg/kg/d, which was the dose used in subsequent experiments. To further explore the protective effect of isoquercitrin on denervated muscle atrophy, we analyzed muscle proteolysis via the ubiquitin–proteasome pathway, mitophagy, and muscle fiber type conversion. Isoquercitrin significantly inhibited the denervation-induced overexpression of two muscle-specific ubiquitin ligases—muscle RING finger 1 and muscle atrophy F-box, and reduced the degradation of myosin heavy chains in the target muscle. Following isoquercitrin treatment, mitochondrial vacuolation and autophagy were inhibited, as evidenced by reduced level of autophagy-related proteins (ATG7, BNIP3, LC3B and PINK1); slow-to-fast fiber type conversion in the target muscle was delayed via triggering expression of peroxisome proliferator-activated receptor γ coactivator 1α; and the production of reactive oxygen species (ROS) in the target muscle was reduced, which might be associated with the upregulation of antioxidant factors (SOD1, SOD2, NRF2, NQO1, and HO1) and the downregulation of ROS production-related factors (Nox2, Nox4, and DUOX1). Furthermore, isoquercitrin treatment reduced the levels of inflammatory factors—interleukin-1β, interleukin-6, and tumor necrosis factor-α—in the target muscle and inactivated the JAK/STAT3 signaling pathway. Overall, isoquercitrin may alleviate skeletal muscle atrophy and mitophagy, and reverse the slow-to-fast fiber type conversion following denervation via inhibition of oxidative stress and inflammatory response. Our study findings enrich the knowledge regarding the molecular regulatory mechanisms of denervated muscle atrophy and provide a scientific basis for isoquercitrin as a protective drug for the prevention and treatment of denervated muscle atrophy.